Triacylglycerol-, wax ester- and sterol ester-hydrolases in midgut of Atlantic salmon (Salmo salar) - Bogevik, Andre S; Tocher, Douglas R; Waagbo, Rune; Olsen, Rolf E (Aquaculture Nutrition, 2008)
Bile salt-dependent lipase (BSDL) is assumed to be the predominant lipid hydrolase in fish digestive tracts where it hydrolyses dietary triacylglycerols (TAG), sterol esters (SE) and wax esters (WE). BSDL is known to hydrolyse TAG at much faster rates than SE and WE in both fish and mammals. An assay for BSDL has previously been developed for rainbow trout (Oncorhynchus mykiss). However, this setup may not be valid in other fish species. Accordingly, the present study aimed at optimizing previous assays in rainbow trout for use on intestinal luminal contents of Atlantic salmon (Salmo salar L.). Crude intestinal extracts from midgut were desalted before the assay and concentrated bile salts supplemented. In general, the rank order for the degree of hydrolysis in Atlantic salmon was TAG > WE > SE. The optimal assay conditions were determined as being 100 lg protein, 125 lM lipid substrate and 20 mM bile salt (taurocholate) during the 4 h of incubation. Atlantic salmon and rainbow trout of 1500 g showed similar lipolytic activity, while salmon smolts of 300 g showed a significantly lower activity. Furthermore, the inhibition of intestinal lipase activities, especially triacylglycerol hydrolase and sterol ester hydrolase, observed in trout intestinal extracts at bile salt concentrations around 10 mM, was not observed in salmon. This could indicate that the activities in these two salmonids may display different enzyme biochemistry.